4
$\begingroup$

Can someone show the way to proof that $$\cos(x+y) = \cos x\cdot\cos y - \sin x\cdot\sin y$$ and $$\cos^2x+\sin^2 x = 1$$ using the definition of $\sin x$ and $\cos x$ with infinite series. thanks...

$\endgroup$
  • $\begingroup$ I think this will helpful math.stackexchange.com/questions/57675/… $\endgroup$ – iostream007 May 29 '13 at 11:08
  • $\begingroup$ Use the Cauchy product and simplify. $\endgroup$ – xavierm02 May 29 '13 at 11:15
  • 1
    $\begingroup$ @iostream007, that question is about proving the infinite series; this question is about using the infinite series. $\endgroup$ – Gerry Myerson May 29 '13 at 13:03
5
$\begingroup$

Let me do a different one. Begin with $$ \sin x = \sum_{k=0}^\infty \frac{(-1)^k x^{2k+1}}{(2k+1)!}, \qquad \cos x = \sum_{k=0}^\infty \frac{(-1)^k x^{2k}}{(2k)!} $$ So compute $$\begin{align} \sin(x+y) &= \sum_{k=0}^\infty \frac{(-1)^k(x+y)^{2k+1}}{(2k+1)!} \\ &= \sum_{k=0}^\infty \frac{(-1)^k}{(2k+1)!}\sum_{j=0}^{2k+1} \binom{2k+1}{j} x^j y^{2k+1-j} \\ &= \sum_{k=0}^\infty (-1)^k\sum_{j=0}^{2k+1} \frac{1}{j!(2k+1-j)!} x^j y^{2k+1-j} \\ &= \sum_{j=0}^\infty \frac{x^j}{j!}\sum_k \frac{(-1)^k}{(2k+1-j)!} y^{2k+1-j} \end{align}$$ where the inner sum is over all $k$ such that $2k+1 \ge j$. Consider two cases for the inner sum, $j$ even and $j$ odd.

If $j=2n$, then $2k+1 \ge j$ iff $2k+1 \ge 2n$ iff $k \ge n$. So the $k$-sum is: $$ \sum_{k=n}^\infty \frac{(-1)^k}{(2k+1-2n)!} y^{2k+1-2n} $$ Use change of variables $i=k-n$ to get $$ \sum_{i=0}^\infty \frac{(-1)^{i+n}}{(2i+1)!} y^{2i+1} = (-1)^n \sin y . $$

If $j=2n+1$, then $2k+1 \ge j$ iff $2k+1 \ge 2n+1$ iff $k \ge n$. So the $k$-sum is $$ \sum_{k=n}^\infty \frac{(-1)^k}{(2k+1-2n-1)!}y^{2k+1-2n-1} $$ Again use change of variables $i=k-n$ to get $$ \sum_{i=0}^\infty \frac{(-1)^{i+n}}{(2i)!} y^{2i} = (-1)^n \cos y. $$ So finally we have $$ \sin(x+y) = \sum_{n=0}^\infty \frac{(-1)^n x^{2n}}{(2n)!} \sin y +\sum_{n=0}^\infty \frac{(-1)^n x^{2n+1}}{(2n+1)!}\cos y = \cos x \sin y + \sin x \cos y. $$

$\endgroup$
2
$\begingroup$

In both cases, you'll want to use the Cauchy product, and the binomial theorem will be useful (for at least the first one), too. I leave the second one to you.

For the first one, $$\begin{align}\sin x\cdot\sin y &= \left(\sum_{n=0}^\infty\frac{(-1)^nx^{2n+1}}{(2n+1)!}\right)\cdot\left(\sum_{n=0}^\infty\frac{(-1)^ny^{2n+1}}{(2n+1)!}\right)\\ &= \sum_{n=0}^\infty\left(\sum_{k=0}^n \frac{(-1)^kx^{2k+1}}{(2k+1)!}\cdot\frac{(-1)^{n-k}y^{2(n-k)+1}}{(2(n-k)+1)!}\right)\\ &= \sum_{n=0}^\infty\left(\sum_{k=0}^n \frac{(-1)^nx^{2k+1}y^{2(n+1)-(2k+1)}}{(2k+1)!(2(n+1)-(2k+1))!}\right)\\ &= \sum_{n=0}^\infty\frac{(-1)^n}{(2(n+1))!}\left(\sum_{k=0}^n\frac{(2(n+1))!x^{2k+1}y^{2(n+1)-(2k+1)}}{(2k+1)!(2(n+1)-(2k+1))!}\right)\\ &= \sum_{n=0}^\infty\frac{(-1)^n}{(2(n+1))!}\left(\sum_{k=0}^n\binom{2(n+1)}{2k+1}x^{2k+1}y^{2(n+1)-(2k+1)}\right)\\ &= -\sum_{n=0}^\infty\frac{(-1)^{n+1}}{(2(n+1))!}\left(\sum_{k=0}^n\binom{2(n+1)}{2k+1}x^{2k+1}y^{2(n+1)-(2k+1)}\right)\\ &= -\sum_{n=1}^\infty\frac{(-1)^n}{(2n)!}\left(\sum_{k=0}^{n-1}\binom{2n}{2k+1}x^{2k+1}y^{2n-(2k+1)}\right),\end{align}$$ whence $$-\sin x\cdot\sin y=\sum_{n=1}^\infty\frac{(-1)^n}{(2n)!}\left(\sum_{k=0}^{n-1}\binom{2n}{2k+1}x^{2k+1}y^{2n-(2k+1)}\right).$$

You can do some of the same sorts of manipulations to see that $$\cos x\cdot\cos y = 1+\sum_{n=1}^\infty\frac{(-1)^n}{(2n)!}\left(\sum_{k=0}^n\binom{2n}{2k}x^{2k}y^{2n-2k}\right).$$ On the other hand, the binomial theorem shows us that for $n\ge 1$ we have $$(x+y)^{2n} = \sum_{j=0}^{2n}\binom{2n}jx^jy^{2n-j},$$ and splitting the right-hand side into two sums--one for even $j$ and one for odd $j$--gives us $$(x+y)^{2n} = \left(\sum_{k=0}^{n}\binom{2n}{2k}x^{2k}y^{2n-2k}\right)+\left(\sum_{k=0}^{n-1}\binom{2n}{2k+1}x^{2k+1}y^{2n-(2k+1)}\right).$$ Can you put the pieces together and fill in the omitted steps/justifications?

$\endgroup$
1
$\begingroup$

The functions $\sin$ and $\cos$, defined by the Taylor series have the following properties:

$$\begin{cases} \sin'=\cos, & \sin 0=0\\ \cos'=-\sin, & \cos 0=1 \end{cases}$$

These properties are easy consequences of the definitions as power series, that can be differentiated term by term; moreover we know that the convergence radius (which is infinite, for $\sin$ and $\cos$) doesn't change when differentiating.

If we now consider the function $$h(x)=(\sin x)^2 + (\cos x)^2$$ we have, by the chain rule, $$ h'=2\sin\cdot\sin'+2\cos\cdot\cos'=2\sin\cdot\cos-2\cos\cdot\sin=0 $$ so $h$ is constant. Since $h(0)=0^2+1^2=1$, we have proved that, for all $x$, $$ (\sin x)^2+(\cos x)^2=1 $$

How do you get $\cos(x+y)=\cos x\cos y-\sin x\sin y$? Just observe that when $f$ and $g$ are functions defined and differentiable over the whole real line, such that $$f'=g,\qquad g'=-f,$$ these functions are uniquely determined as linear combinations of $\sin$ and $\cos$ by their values at $0$.

(Drawn from Lang's Introduction to mathematical analysis.)

$\endgroup$
  • 1
    $\begingroup$ Of course you can use the series to get some other characterization of the trig functions, and then solve the problem using that other characterization. But a better answer would use the series directly. $\endgroup$ – GEdgar May 29 '13 at 14:28
  • 1
    $\begingroup$ @GEdgar I appreciate the way you present your long computation; but I think that a proof like this is worthy because it hides the hairy details under the cover of higher level tools. $\endgroup$ – egreg May 29 '13 at 15:26
1
$\begingroup$

I like egreg's answer, and I pick up where he left off. Fix $y \in \mathbb{R}$. Define $$F(x) = \sin(x+y) - \sin(x) \cos(y) - \cos(x) \sin(y)$$

We want to show that $F(x) = F'(x) = 0$ for all real numbers $x$. Now

\begin{align*} & F'(x) = \cos(x+y) - \cos(x) \cos(y) + \sin(x) \sin(y) \\ \implies & F''(x) = -\sin(x+y) + \sin(x) \cos(y) + \cos(x) \sin(y) \\ \implies & F(x) + F''(x) = 0 \\ \implies & 2F'(x) F(x) + 2 F'(x) F''(x) = \frac{d}{d\ x} [(F(x))^2 + (F'(x))^2] = 0 \end{align*}

It is clear that $F$ is infinitely differentiable, so the Mean Value Theorem grants us that $H(x) = (F(x))^2 + (F'(x))^2$ is a constant function. Since we know from their power series definitions that $\sin(0) = 0$ and $\cos(0) = 1$, we have $F(0) = F'(0) = 0$, hence $H(x) = H(0) = 0$ for all $x \in \mathbb{R}$. Now this implies that $F(x) = F'(x) = 0$ on $\mathbb{R}$ as well, and so we now know what $\sin(x+y)$ and $\cos(x+y)$ are (just look at the expressions for $F$ and $F'$ above).

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.